2014
DOI: 10.23986/afsci.40936
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences of apples in Estonia and changes in attitudes over five years

Abstract: Apple preferences of Estonian consumers (n=336 in 2007 and 332 in 2012) were determined regarding apple origin, production method and different quality attributes. The aim was to find out whether apple preferences of young people raised in a capitalistic system differ from older people raised in the Soviet Union and also to determine if and how these preferences have changed over five years. The majority of the respondents preferred domestic apples (91% and 81% in 2007 and 2012, respectively), the main motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…Knowledge about products' origin is a factor that can potentially modify a consumer's evaluation and perception of such products (Gázquez-Abad et al 2012). The literature indicates that consumers consider local origin to be synonymous of high quality, although this can change in relation to both the product considered and the geographical context (Moor et al 2014;Papanagiotou et al 2013;Font et al 2011;Dekhili and d'Hauteville 2009;Ekelund et al 2007). According to the literature, organic certification is also considered an important predictor of consumers' choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge about products' origin is a factor that can potentially modify a consumer's evaluation and perception of such products (Gázquez-Abad et al 2012). The literature indicates that consumers consider local origin to be synonymous of high quality, although this can change in relation to both the product considered and the geographical context (Moor et al 2014;Papanagiotou et al 2013;Font et al 2011;Dekhili and d'Hauteville 2009;Ekelund et al 2007). According to the literature, organic certification is also considered an important predictor of consumers' choice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other studies, taste is also considered an important quality element that has a positive and significant influence on consumers' buying intentions. For fruit and vegetables, taste is the most important attribute consumers take into account, independent of age, gender, or the number of fruits consumed per week (Moor et al 2014;Péneau et al 2006;Jönson 2004). Finally, price is considered important in affecting consumer choice; on the one hand, it is perceived as a signal to infer food quality (Röhr et al 2005), and on the other hand, it represents a barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For fruits and vegetables, freshness, taste, and aroma are the most important attributes consumers take into account (Moor et al 2014). As examples, House et al (2011) and Gao et al (2011) found that sweetness, shape, acidity, and flavor are the most important factors influencing consumers' willingness to buy mandarins.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fifthly, the factor analysis includes purchasing place because it will infl uence the apple price. Péneau, et al (2006) size, flavor, appearance, aroma, freshness, cultivar, organic Rahayu, et al (2012b) size, price, color, texture, sponge nets packaging Skreli & Imami (2012) size, varieties/cultivar, apple origin (local and imported) Widyadana, et al (2013) size, flavor, appearance, color, crispness, aroma, hygiene Moor et al (2014) flavor, price, appearance, health benefi ts This study s i z e ( w e i g h t ) , f l a v o r, a p p e a r a n c e , c u l t i v a r, texture, aroma, freshness, juiciness. We include purchasing place in the analysis…”
Section: Figure 1 Consumers' Equilibrium Onmentioning
confidence: 99%